New ST623 of Cryptococcus neoformans isolated from a patient with non-Hodgkin’s lymphoma in the Brazilian Amazon - Lucyane Mendes Silva (Annals of Clinical Microbiology and Antimicrobials, 2020)
Abstract Background Cryptococcosis is a disease of wide geographic distribution. It is most critical when it affects immunocompromised patients, with AIDS, tuberculosis or other diseases that require prolonged hospitalization. Methods This study described a case report, molecular epidemiology, the phylogenetic relationship, along with antifungal susceptibility test of a new ST 623 of C. neoformans isolated in a patient with non-Hodgkin’s Lymphoma, from Manaus, Brazil. Results The new C. neoformans was susceptible to all antifungal drugs tested. Our results showed that ST623 new clone has no evident evolutionary proximity to any other ST of the VNI subtype group identified in Brazil. Conclusions In the context of phylogenetic analysis, this new genotype belongs to VNI subtype, and subsequencing complete genome studies are necessary to better understand the phylogenetic relationships amongst STs in this group.